Adverse events unlikely after fine-needle aspiration biopsies of thyroid nodules in patients on low-dose aspirin: a prospective controlled systematic single center analysis - Cordes, Michael; Götz, Theresa Ida; Kuwert, Torsten; Schmidkonz, Christian (Nuklearmedizin - NuclearMedicine, 2023)
Aim Our aim was to test the assertion that in terms of rate or severity level, adverse events (AEs) after fine-needle aspiration biopsies (FNABs) of thyroid nodules are unfazed by daily low-dose (100 mg) aspirin (acetylsalicylic acid, ASA) intake.Methods We selected 268 patients for study, grouped as ASA-treated (PASA, n=78) or control (PCtrl, n=190) subjects. Controls received no antithrombotic medication. AE rates and severities were then analyzed based on patient- and nodule-related factors. We also compared group rates of non-diagnostic cytology results.Results AEs arising after FNABs (PASA, 5%; PCtrl, 8%) did not differ significantly by group in rate (p=0.4873) or severity level (p=0.3399). All were classifiable as minor incidents, none warranting any intervention.Conclusions The data from the present study suggest, AEs after FNABs of thyroid nodules seldom occur and qualify as minor incidents. Such procedures may be safely conducted in patients taking daily low-dose ASA. There is no evidence to support preemptive therapeutic withdrawal.
Keywords: thyroid nodules; fine-needle aspiration biopsy; acetylsalicylic acid; ASA; antithrombotic agent